Method for melt processing textile waste and product obtained by said method
By chemically pretreating and thermally processing textile waste, nano-scale cellulose composite materials are prepared, which solves the problems of complex recycling process and high energy consumption in the existing technology, and realizes environmentally friendly and efficient textile recycling and composite material production .
Patent Information
- Application Number
- CN202380049878.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-22
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art requires complete separation or depolymerization of components in textile recycling, resulting in complex processes, high energy consumption and unenvironmentality.
By chemically pretreating and thermomechanizing textile waste, composites containing thermoplastic polymers and cellulose are prepared, reducing the size of cellulose fibers to the nanoscale and forming a well-dispersed polymer composite.
This method simplifies the recycling process, reduces energy consumption, reduces pollution, and can effectively utilize textile waste to produce composite materials with high cellulose content.
Smart Images

Figure CN119421774A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a method for melt processing of textile waste as defined in the preambles of the independent claims, a composite material obtained by the method, a recycled product obtained by the method, a 3D printable filament obtained by the method and a 3D printed recycled product obtained by the method. Background Art
[0002] For environmental purposes, there is an increasing demand for means and methods for recycling waste materials. This also becomes relevant for textile waste, in order to produce new products from waste materials in an efficient and environmentally friendly manner. Today, some methods for recycling and / or separating the various components of textile waste are being used. However, current methods have limitations and disadvantages, for example, for textile waste that can be used to contain both thermoplastic polymers and cotton and / or cellulosic fabrics.
[0003] CN-A-113005536 discloses nanoscale plastic particles and methods for preparing the same involving dissolving plastic powder in an organic solvent. US-A-2019136455 discloses a cellulosic material and a method for making the cellulosic material in the case of cotton recycling, wherein the method involves dissolving or suspending the active ingredient in a medium comprising the cellulosic material by contacting the cotton fabric with an oxidizing system to obtain an oxidized cotton material. US-A-20210269969 discloses a method for separating a cellulose portion from a raw material composition comprising polyester and cellulose, which involves using a hydrolyzate to alkalize a polyester / cellulose blend. WO2021 / 181007 discloses a method for separating cellulosic fibers and non-cellulosic fibers from a mixed fiber textile material, comprising mechanical decomposition of the textile material and subsequent acid treatment, followed by an alkali treatment. IN-A-202011022177 discloses the production of nanofibers from waste plastic bottles.
[0004] Literature shows that most textile sorting processes have so far focused on cotton or polyester cotton (Palme et al. Text. Cloth. Sustain 2017, 3 (4).) and subsequent recovery through chemical routes such as: i) dissolution and wet spinning (Liu et al., Carbohydrate Polymers 206 (2019) 141–148), ii) extraction of cellulose nanocrystals (Wang et al. Carbohydrate polymers 2017, 157, 945-952; Zhong et al. Carbohydrate Polymers 240 (2020) 116283), iii) chemical dissolution of polyester and recovery of cellulose (S. Yousef et al. Journal of Cleaner Production 254 (2020) 12007). Therefore, in Sweden, Renewcell's efforts to recycle cotton or polyester cotton into new textile fibers have attracted great interest, in which a chemical process breaks down the textile into monomers or polymers, which are spun into fibers ( https: / / www.renewcell.com / en / section / our-technology / ). Meanwhile, Mathew and collaborators developed green fractionation of cellulose and polymers from textile blends to the nanoscale (Ruiz Caldas et al., ACS Sust Chem Eng. 2022, 10: 3787), and they recently produced CNCs from undyed and dyed cotton and its blends with polyester and acrylic. It was also noted that colored nanocellulose could be obtained by this method.
[0005] A problem with prior art solutions is that, for recycling purposes, complete separation or depolymerization of the components is usually required, which requires an affordable, energy demanding and complex manufacturing process.Therefore, there is a need for improved, more environmentally friendly and simplified methods for recycling textiles.
[0006] Carette et al. (J Polym Environ 2021; 29: 662-671) reported the use of PET from bottles and cellulose from textiles in the manufacture of composites. The components came from different sources and the PET was not derived from textiles. Wang et al. (J Appl Polym Sci 2013; 128: 3555-3563) used waste cotton fabrics in combination with thermoplastic PU from non-textile sources. No chemical treatment steps were included in the process. WO 2022 / 112719 A1 used fibers from textiles in combination with polymers from non-textile sources. In these studies, the fiber size was kept in the same range (micrometers) as the feed textile.
[0007] The method of the present disclosure enables the use of polymer and cellulose fibers from the same fabric. Furthermore, a chemical pretreatment step followed by thermomechanical processing enables fiber reduction of cotton fibers from typical diameters (about 100 microns) down to 100 nm (even down to the nanoscale). Summary of the invention
[0008] Therefore, since prior art methods typically utilize complete chemical separation or depolymerization of components for recovery, the present inventors have seen the possibility of partially fractionating textiles into suitable mixtures before conversion into new products.
[0009] An object of the present disclosure is to mitigate, alleviate or eliminate one or more of the above-mentioned deficiencies and disadvantages in the prior art and to solve at least the above-mentioned problems.
[0010] According to a first aspect, a method is provided for melt processing of textile waste, wherein the textile waste comprises: (1) at least one thermoplastic polymer material, such as polyurethane, polyester, nylon or elastane; and (2) at least one cellulose-containing material, such as cotton textiles, cotton blends with synthetic polymers or natural polymers, textiles based on regenerated cellulose, the method being suitable for preparing a composite material, comprising the following steps:
[0011] (a) Chemical pre-treatment of textile waste;
[0012] (b) subjecting the chemically pretreated material of step (b) to thermomechanical processing, including melt compounding, optionally including the addition of recycled PET, plasticizers such as glycerol, PEG and vegetable oils, and / or toughening polymers such as natural rubber and polyurethane;
[0013] Thereby a composite material is obtained comprising a well-dispersed polymer composite and / or nanocomposite, wherein the at least one thermoplastic polymer material substantially constitutes the matrix phase and the at least one cellulose-containing material substantially constitutes the reinforcement phase of the composite material.
[0014] Thus, a scheme for melt processing textiles to prepare a composite in which a thermoplastic polymer acts as a matrix and cotton fibers act as a reinforcing phase has been developed as a commercially viable processing route for textile recycling. Typically, thermoplastic polymer materials and cellulose-containing materials come from the same textile waste, i.e., from the same textile source, which is advantageous by simplifying the recycling process. A pretreatment utilizing a chemical process approach will be used to promote the melt composite process (i.e., melt processing), and to optimize the production of a one-step process in which well-dispersed polymer composites and nanocomposites are not separated into multiple components. This can be controlled by keeping the reduction in weight between the feed fabric and the composite to less than 5% by weight. Melt processing will not chemically modify the material generally, but the material will be physically modified into a uniform composite or nanocomposite (by reducing the size of the cellulose fibers). However, if additional chemicals are added to produce grafting on the cellulose or polymer phase, chemical modification can be performed. In addition, the process is green and provides a sustainable recycling method for textile waste. For example, there is an advantage in that there is no secondary pollution from the recycling process and all fiber components of post-consumer textiles are used by converting into new products (i.e. composites and thereafter 3D printable filaments). The process can also be extended to other cotton blends containing nylon, spandex, etc.
[0015] According to some embodiments, the chemical pretreatment is selected from at least one of the following approaches:
[0016] (i) partially dissolving at least one thermoplastic polymer material using a 1:1 to 1:2 mixture of TFA (trifluoroacetic acid) and DCM (dichloromethane);
[0017] (ii) subjecting any cellulose present in the at least one thermoplastic polymer material and / or the at least one cellulose-containing material to citric acid hydrolysis; and
[0018] (iii) subjecting any cellulose present in the at least one thermoplastic polymer material and / or the at least one cellulose containing material to a tempo-mediated oxidation.
[0019] Thus, an alternative approach for chemical pretreatment is presented, which allows only partial classification of textile materials, i.e., by reducing the size and phase of one of the components in the textile while keeping the other component intact. These are three independent processing approaches with different advantages. "Thermoplastic polymer material" may also be referred to as "thermoplastic polymer PET phase". Procedure (i) is most advantageous for cotton blends, while procedures (ii) and (iii) are advantageous for pure cotton and cotton blends. The chemical pretreatment of the present disclosure causes some changes in surface chemistry, such as oxidation, while melt processing itself will only cause homogenization of the mixture and reduction of the cellulose phase size. In the case of procedures (ii) (citric acid approach) and (iii) (tempo approach), the melt processing step can produce nanoscale cellulose in the product. In this context, "nanoscale" will refer to any cellulose (or other material) having a size less than 100nm. Therefore, for particles referred to as "nanosize" or "nanoscale", it must be less than 100nm in at least one dimension.
[0020] Route (i) is an organic solvent based process, while routes (ii) and (iii) are water based processes. In route (i), the polymer phase is partially dissolved (by controlling the amount and ratio of the solvents used), and the cellulose phase remains unchanged. In routes (ii) and (iii), the cellulose fraction is modified and / or hydrolyzed, while the polymer phase remains unchanged.
[0021] Chemical treatment removes non-crystalline cellulose and / or adds chemical groups to cellulose (sulfate, citrate, carboxyl) and / or makes the cellulose fiber structure less compact (due to oxidation or esterification which reduces interactions). Physically, the changes are associated with a weakening of the cellulose fiber structure by cutting it across or along the fiber length to produce fibers / fibrils with a shorter diameter (50 μm to 100 nm) than the feed.
[0022] Thus, chemical pretreatment approaches (ii) and (iii) (e.g., as shown in Example 8) are successful in functionalizing cellulose in textiles and textile blends with chemical groups for ionic crosslinking or interaction with water contaminants. During thermomechanical processing, the chemical groups on the cellulose phase will promote fibrillation to the nanoscale.
[0023] According to some embodiments, chemical pretreatment according to route (ii) and / or (iii) is followed by fibrillation using mechanical processing and bead processing using (j) thermally induced phase separation or (jj) oven drying (as exemplified in Example 4), followed by subsequent thermomechanical processing. The fibrillation step has the effect of converting the cotton into nanoscale cellulose, and bead preparation is a process that develops the pellets for subsequent thermomechanical processing.
[0024] According to some embodiments, the textile waste is melt processed at a temperature below 250°C at ambient pressure.
[0025] Thus, thermoplastic polymers suitable for the disclosed method are used.
[0026] According to some embodiments, the cellulose-containing material comprises cellulose I and / or cellulose II polymorphs.
[0027] For this purpose, suitable cellulose-containing materials are used.
[0028] According to some embodiments, the textile waste is selected from: recycled textile clothing or shoes; polyester blends; cotton blends comprising polyester, elastane, cellulose, polyurethane and / or nylon; chopped polyester cotton; and chopped acrylic cotton.
[0029] Thus, materials from suitable sources are used as starting materials. Textile materials from other sources may also be used, as long as the other requirements presented in the present disclosure are met.
[0030] According to some embodiments, the method comprises using the composite material obtained in step (b) for processing by injection molding, compression molding or any other melt processing method, thereby obtaining a recycled product.
[0031] The composite material obtained is thereby processed and used without subsequent preparation for 3D printing.
[0032] According to some embodiments, the method further comprises subjecting the composite material obtained in step (b) to filament processing, including filament extrusion to produce 3D printable filaments.
[0033] Thus, a composite material for subsequent 3D printing was prepared.
[0034] According to some embodiments, the method includes using the obtained 3D printable filament for 3D printing, thereby obtaining a 3D printed recycled product.
[0035] Thus, the final product of 3D printing is obtained.
[0036] According to a second aspect, a composite material comprising well-dispersed polymer composites and / or nanocomposites is provided, wherein (1) at least one thermoplastic polymer material substantially constitutes a matrix phase, and (2) at least one cellulose-containing material substantially constitutes a reinforcement phase of the composite material, wherein the at least one thermoplastic polymer and the at least one cellulose-containing material are derived from the same textile waste.
[0037] Thus, a new composite material is provided by the new method, which provides advantages in terms of process efficiency, cost, environmental aspects and material properties. In addition, a composite material with a high cellulose content is obtained. For microcomposites, the cellulose content can be up to 50%, up to 60%, or even up to 75%, and for nanocomposites, the cellulose content can be up to 20%. In addition, by using the composite material as a masterbatch, the composite mixture can be diluted with other polymers, thereby reducing the amount of cellulose when necessary.
[0038] The composite material will undergo physical changes as the synthetic fibers are partially melted and lose their fiber structure and become the matrix phase. During melt compounding, the length and diameter of the cellulose fibers decrease. Generally, no chemical changes are expected in cotton or synthetic fibers.
[0039] According to some embodiments, at least one thermoplastic polymer material is derived from polyurethane, polyester, nylon, cellulose or elastane, and at least one cellulose-containing material is derived from cotton textiles, cotton blends with synthetic or natural polymers, or regenerated cellulose-based textiles.
[0040] Thereby, suitable materials are provided to obtain composite materials.
[0041] According to some embodiments, the composite material comprises (i) recycled PET, (ii) plasticizers such as glycerol, PEG and vegetable oils, and / or (iii) toughening polymers such as natural rubber and polyurethane.
[0042] Thus, by including a plasticizer in the melt compound, homogenization during melt processing is promoted. In addition, the product is made more flexible. In addition, the toughening agent will help make the composite less brittle and can be used to adjust the toughness of the composite. Therefore, by adding recycled PET, the composition of the composite can be adjusted according to the masterbatch principle discussed above, that is, by using the composite composition as a masterbatch and mixing it with other polymers to adjust the composition. Recycled PET can be added from other sources and processing routes (see, for example, Ruiz Caldas et al., ACS Sust Chem Eng. 2022, 10: 3787).
[0043] According to some embodiments, the thermoplastic polymer can be melt processed at temperatures below 250°C at ambient pressure.
[0044] According to some embodiments, the cellulose-containing material comprises cellulose I and / or cellulose II polymorphs.
[0045] According to some embodiments, (1) the thermoplastic polymer material is fractionated and the cellulose-containing polymer is intact, or (2) the thermoplastic polymer is intact and the cellulose-containing material is fractionated, compared to the original textile waste. Thus, as a result of the chemical pretreatment according to the present disclosure, a partially fractionated composite material is obtained, the fractionated components thereby exhibiting reduced size or phase.
[0046] According to some embodiments, the composite material comprises nano-sized cellulose, which can be obtained by fractionating a cellulose-containing material according to, for example, route (ii) or (iii) according to the present disclosure. Nano-sized cellulose can be advantageous for subsequent products based on the composite material of the present disclosure.
[0047] According to some embodiments, the composite material is in the form of pellets.
[0048] Thereby, recycled composite pellets may be provided as a product.The pellets obtained according to the present disclosure will typically be in the form of beads of 0.5 to 1 cm in diameter containing up to 50% by weight of cellulose.
[0049] According to a third aspect, there is provided a recycled product comprising the composite material of the second aspect further melt processed by injection moulding, compression moulding or any other melt processing method.
[0050] Thus, by manufacturing the product using these methods, and changing the shape and form of the composite, a recycled product is obtained from the composite material without any subsequent 3D printing step. At this stage, no physical or chemical changes are expected.
[0051] According to a fourth aspect, there is provided a 3D printable filament for subsequent use in 3D printing to obtain a 3D printed recycled product, comprising the composite material according to the second aspect of the invention further filament processed by filament extrusion.
[0052] Thereby, a 3D printable filament based on the obtained composite material may be provided, which may be defined as a continuous filament with a specified diameter (typically 2.85 mm or 1.75 mm) that may be used in a 3D printer for in-fused filament deposition.
[0053] According to a fifth aspect, there is provided a 3D printed recycled product comprising the 3D printable filament of the fourth aspect which has been further 3D printed.
[0054] Thus, a 3D printed recycled product is provided. 3D printing will have the effect of structuring the product, but no physical or chemical changes are expected. However, 3D printed products made from recycled textiles are unique.
[0055] According to some embodiments, the 3D printed recycled product is selected from a shoe, an interior design product, an accessory, or a water filter.
[0056] In the case of water filters, the surface chemistry of cellulose has a beneficial effect, making the chemical treatment of textiles highly relevant and unique. In addition, any other product types that can be 3D printed based on composite materials are also included in the scope of the present disclosure.
[0057] The effects and features of the second to fifth aspects are largely similar to those described above in conjunction with the first aspect. The embodiments mentioned in relation to the first aspect are largely compatible with the second to fifth aspects.
[0058] The products and materials defined in the second to fifth aspects may be obtained, for example, by the method of the first aspect.
[0059] The present disclosure will become apparent from the specific embodiments given below. The specific embodiments and specific examples disclose preferred embodiments of the present disclosure only by way of illustration. It will be appreciated by those skilled in the art from the guidance of the specific embodiments that changes and modifications may be made within the scope of the present disclosure.
[0060] Therefore, it should be understood that the disclosure disclosed herein is not limited to the specific composition of the described product or the step of the described method, because such product and method can change.It should also be understood that the terms used herein are only for the purpose of describing a specific embodiment, and are not intended to be restrictive.It should be noted that, as used in the specification and the appended claims, unless the context clearly indicates otherwise, nouns and "described" modified by quantifiers are intended to mean one or more of the elements present.Therefore, for example, mentioning "unit" or "the unit" can include several devices, etc. In addition, the words "comprise", "include", "contain" and similar words do not exclude other elements or steps.
[0061] definition
[0062] The term "well dispersed" should be interpreted as the mixture / composite being homogeneous. It also means that all components of the composite are uniformly dispersed and distributed throughout the material. This property is important for good and reliable performance of the material and does not show sample-to-sample or batch-to-batch variations.
[0063] The term "matrix" should be interpreted as the continuous phase, which acts as a binder phase in a composite material, while the term "reinforcement" is the dispersed phase and brings added mechanical properties to the matrix. Thus, the "matrix phase" would be the continuous binder phase in the composite in which the fibers are dispersed, and the "reinforcement phase" is the fiber component in the composite and generally has a higher stiffness than the matrix phase.
[0064] The term "PET phase" should be interpreted as the polyethylene terephthalate portion of the textile. BRIEF DESCRIPTION OF THE DRAWINGS
[0065] The above objects as well as additional objects, features and advantages of the present disclosure will be more fully understood by referring to the following illustrative and non-limiting detailed description of example embodiments of the present disclosure when taken in conjunction with the accompanying drawings.
[0066] Figure 1 A schematic diagram of a method according to the present disclosure indicating the method steps as well as the obtained products is shown.
[0067] Figure 2 An overview of the thermomechanical processing steps of the overall method is shown.
[0068] Figure 3 Schematic diagram of citric acid-mediated hydrolysis of cotton-based textiles and the tempo-mediated alternative pathway for chemical pretreatment are shown.
[0069] Figure 4 FTIR data of the chemical functional groups of cellulose from pathway ii are shown. DETAILED DESCRIPTION
[0070] The present disclosure will now be described with reference to the accompanying drawings showing preferred exemplary embodiments of the present disclosure. However, the present disclosure may be implemented in other forms and should not be construed as being limited to the embodiments disclosed herein. The disclosed embodiments are provided to fully convey the scope of the present disclosure to the skilled person.
[0071] Figure 1A schematic diagram of a method for melt processing of textile waste according to the present disclosure is shown, wherein, as starting material, textile waste is used, such as recycled textile clothes or shoes; polyester blends; cotton blends containing polyester, elastane, cellulose, polyurethane and / or nylon; chopped polyester cotton; and chopped acrylic cotton. The textile waste comprises: at least one thermoplastic polymer material, such as polyurethane, polyester, nylon, cellulose or elastane; and at least one cellulose-containing material, such as cotton textiles, cotton blends with synthetic polymers or natural polymers, or textiles based on regenerated cellulose. Typically, thermoplastic polymer materials have the ability to be melt processed at temperatures below 250° C. at ambient pressure, which makes them suitable for the method of the present disclosure and the thermomechanical processing steps used. The cellulose-containing material typically has a cellulose I and / or cellulose II polymorph, which has proven to be advantageous.
[0072] In the first chemical pretreatment step, the textile waste is only partially dissolved, i.e. complete decomposition is avoided. This can be achieved by any of the disclosed alternative pathways:
[0073] (i) partially dissolving at least one thermoplastic polymer using a 1:1 to 1:2 mixture of TFA (trifluoroacetic acid) and DCM (dichloromethane);
[0074] (ii) subjecting the cellulose in the at least one thermoplastic polymer material and / or the at least one cellulose-containing material to citric acid hydrolysis, wherein the concentration of the citric acid will typically be in the range of about 80% to 85% by weight and the temperature (under standard conditions) will typically be in the range of 90°C to 100°C; and
[0075] (iii) Tempo-mediated oxidation of cellulose in polyester cotton, wherein the ratio between textile and reagent is an important parameter. The textile material is chemically treated at a concentration of 2 wt % in an aqueous medium using 0.1 mmol TEMPO, 0.1 g NaBr and 10 mmol NaClO per gram of cellulose at a pH of 10 maintained using a 2M NaOH solution. After 4 hours, the oxidized material is thoroughly washed until the conductivity is less than 10 μS / cm. The ratio can typically vary between 5 mol and 10 mol NaClO per gram of cotton / cellulose, and the concentration of the textile on water can range from 1 wt % to 3 wt %.
[0076] Procedure (i) is most favorable for cotton blends, while procedures (ii) and (iii) are favorable for pure cotton and cotton blends. Chemical pretreatment causes some changes in surface chemistry, such as oxidation, while melt processing itself will only cause homogenization of the mixture and a reduction in the size of the cellulose phase (down to 50 nm). For example, oxidation typically changes the hydroxyl and carbonyl or citrate groups in cellulose. This has been determined by chemical analysis (FTIR and NMR). In the case of procedure (iii) (tempo approach), the melt processing step can produce nanoscale cellulose in the product.
[0077] Chemical pretreatment according to route (ii) or (iii) may be followed by intermediate steps involving fibrillation using mechanical processing and bead processing using thermally induced phase separation methods.Thus, intermediate products in the form of cellulose, polymers and / or nanocellulose may be provided.
[0078] Alternatively, chemically treated textiles (2 wt %) in water dispersion were dispersed for 20 minutes using a High-Shear Dispermix (Ystral GmbH, Germany). The obtained dispersion was cast into a film with a thickness of 1 to 2 cm, which was dried overnight in an oven at 60°C. The dried film was cut into small square pellets (1 cm x 1 cm) using a commercial paper cutter and followed by thermomechanical processing. This alternative step is performed after chemical processing and usually requires melting and compounding the two phases into a homogeneous masterbatch or composite.
[0079] Chemical pretreatment (optionally followed by fibrillation and / or bead processing) is followed by a thermomechanical processing step including melt compounding, wherein the addition of further ingredients may be performed. These ingredients include, for example, the addition of (i) recycled PET, (ii) plasticizers such as glycerol, PEG and vegetable oils, and / or (iii) toughening polymers such as natural rubber and polyurethane to promote the homogeneity of the composite material obtained and to adjust the material properties (e.g. flexibility, brittleness and toughness). These properties can be measured by microscopy data and mechanical property data.
[0080] As a result of chemical pretreatment and thermomechanical processing, a composite material is obtained, wherein the composite material comprises a well-dispersed (homogeneous) polymer composite and / or nanocomposite, wherein at least one thermoplastic polymer material substantially constitutes the matrix phase and at least one cellulose-containing material substantially constitutes the reinforcement phase of the composite material.
[0081] Ideally, all components of the composite are uniformly dispersed and distributed throughout the material, which can be measured using microscopy (optical microscopy, scanning electron microscopy, atomic force microscopy, etc.). This property is important for the good and reliable performance of the material and does not show sample-to-sample or batch-to-batch variation. In addition, chemical pretreatment causes some changes in surface chemistry; for example, oxidation, while melt processing itself will cause homogenization of the mixture and reduction in the size of the cellulose phase. In the case of procedures (ii) (citric acid approach) and (iii) (tempo approach), the melt processing step can produce nanoscale cellulose in the product.
[0082] The composite material obtained after the thermomechanical processing step can be used directly, preferably after processing by injection molding, compression molding or any other melt processing method, to obtain a recycled product, for example in the form of pellets. Thus, the composite material can be used to manufacture products using other methods widely used in the polymer industry. This is in addition to the possibility of 3D printing.
[0083] Alternatively, the composite material obtained after the thermomechanical processing undergoes filament extrusion to produce a 3D printable filament. The filament obtained will typically have a diameter of 1.75 mm or 2.85 mm (+ / - 0.05 mm) and be produced at a speed of 2 meters per minute.
[0084] The 3D printable filament obtained after filament extrusion can be provided as is (ie as a saleable end product) and / or provided for subsequent processing, such as 3D printing.
[0085] Alternatively, the 3D printable filament obtained after filament extrusion is used in a 3D printing process to obtain a 3D printed recycled product, such as a shoe, a garment, a garment, an interior design, an accessory, or a water filter. For example, 3D printing can be performed using an Ultimaker S5 (Ultimaker BV, The Netherlands) printer at a temperature of 220° C. However, other printers and conditions may also be used.
[0086] Figure 2 A thermomechanical processing step is disclosed as part of the method of the present disclosure, wherein composite fibers are produced in a melt processing device, possibly by adding reinforcing and / or toughening agents, and the resulting extrudate is cooled in a water bath. The temperature profile during this processing is typically 200°C to 225°C.
[0087] The invention will now be further described with reference to examples of embodiments and process steps.
[0088] Example
[0089] Example 1 - Chemical pretreatment route (i) - Partial dissolution of thermoplastic polymers
[0090] Cotton / polyester blends with different PET contents were used as starting materials.
[0091] Partially dissolved
[0092] PET / cotton (60 / 40) fabric was cut into 2 cm x 2 cm squares. 100 g of the cut fabric portion was dissolved in a TFA+DCM mixture of 1:2 TFA (trifluoroacetic acid) / DCM (dichloromethane). The partially dissolved textile was dried overnight and further ground into a finer powder.
[0093] Example 2 - Chemical pretreatment, step (ii): citric acid hydrolysis
[0094] Cotton and cotton blends with polyester, acrylic or elastane were used as starting materials.
[0095] Esterification and partial hydrolysis of cotton
[0096] Cotton textile fragments are cut into small (<1 cm) pieces and placed in a round-bottom flask containing anhydrous citric acid and water at a concentration of 85% by weight. The ratio of textile to pure citric acid is 1:20 (g / g). The flask is immersed in an oil bath and heated to 100°C while mixing. The mixture is stirred at 300 rpm using an overhead mechanical stirrer until the citric acid is completely dissolved, and then for another seven hours before the reaction, which is quenched by diluting five times with DI water. The quenched mixture is vacuum filtered onto a polyethersulfone (PES) membrane (pore size of 5 μm) to separate the citric acid solution from the solid fraction containing carboxylated cotton fibers and residual acid. The citric acid collected from the first filtration is recovered by rotary evaporation and crystallization. DI water is slowly added to the filter cake to rinse the remaining citric acid from the solid. The filter cake is washed until the conductivity of the filtrate is less than 5 μS / cm. Thus, the washing from this process does not contain ions, so the product is in a neutral medium.
[0097] Textile pieces consisting of mixed fabrics (polyester-cotton or acrylic-cotton) were cut into small square pieces with a side length of <1 cm. An 80 wt% citric acid solution was prepared in a round-bottom flask by dissolving 60 g of anhydrous citric acid in 15 ml of water and heated to >80°C using an oil bath. While heating, 195 mg of FeCl 3 - Equivalent to 0.02mmol FeCl per gram of citric acid 3. 2 g of square pieces were added to the flask and the reaction was allowed to proceed for six hours with a mechanical stirrer mixing at 400 rpm. After six hours, the reaction was quenched by adding about 200 ml of deionized water and allowed to cool at ambient temperature. Longer fibers and a milky suspension were observed. The longer fibers (mainly made of polyester or acrylic fibers) were separated from the milky suspension using a 250 μm sieve and washed thoroughly with DI water. The suspended particles were precipitated and washed by continuous centrifugal cycles until a conductivity of less than 5 μS / cm was reached.
[0098] The filter cake of carboxylated cotton fabric was diluted with DI water to a concentration of approximately 2 wt % and then dispersed in DI water, regardless of the textile source. Figure 3 Schematic diagram showing the citric acid-mediated hydrolysis of cotton-based textiles.
[0099] Processing of Nanocellulose
[0100] Regardless of the source textile, the obtained dispersion was neutralized by adding a few drops of NaOH (aq, 1 M) until a pH of 7.0 was reached, then diluted to 1.0 wt % and fibrillated using a high-pressure microfluidizer (M-110EH, Microfluidics). Five passes through chambers of 400 μm and 200 μm width connected in series were performed at 1000 bar, followed by five passes through chambers of 200 μm and 100 μm width at 1700 bar. After mechanical fibrillation, the obtained dispersion was centrifuged at 10.000 g for 10 minutes and passed through a glass microfiber filter (Ahlstrom- MGF grade, particle retention 0.7 μm) was vacuum filtered to remove traces of non-fibrillated cotton. The final product was a colloidal dispersion of CNCs with surface carboxyl groups (-COONa) in the sodium form.
[0101] Example 3 - Chemical Pretreatment, Procedure (iii): Tempo-mediated Oxidation
[0102] Textile samples with 100% cotton or cotton blends with polyester, acrylic, wool or spandex were cut into 5 cm square pieces. 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO)-mediated oxidation of the textiles (10 mmol hypochlorite per gram of cotton) was performed and cleaned by washing with distilled water (see Figure 3). The concentration of textile in water is 1.5 wt % to 2 wt %. NaClO is poured dropwise while adjusting the pH to 10 with 1 M NaOH and 0.5 M HCl (if necessary). Note: If the target charge density is low or medium, the reaction will stop on its own after several minutes or hours (the color changes from yellow to white when all chemicals are consumed). If the target charge density is 1.6 mmol COO- / g (high charge), the reaction can be quenched by adding deionized water after a minimum of 4 hours. At the end of the reaction, the chemicals are washed off by multiple cycles of deionized water and filtration until the conductivity is less than 5 μS to 10 μS and the pH is about 8 or at least less than 9.
[0103] Finally, the resulting cellulose is filtered and washed several times until the filtered solution is neutral.
[0104] In order to convert oxidized cotton into nanocellulose decomposition, ultrafine grinding is used. A suspension with 1% to 2% by weight from a chemical treatment process is ground with a positive gap to avoid grinding stones. The material is passed through the grinding stones at least 10 times to achieve nanoscale material to form a cellulose phase.
[0105] Example 4 - Processing of Composites and Filaments
[0106] The carboxylated products from Procedure 2 and Procedure 3 (with or without fibrillation) were further used for pellet preparation by following thermally induced phase separation method or oven drying method, which have been found to be efficient and alternative processing routes.
[0107] Thermally Induced Phase Separation (TIPS): The masterbatch of composite spheres was prepared using the TIPS technique. The composite dispersion was added to a 20 ml syringe and manually extruded dropwise into a liquid nitrogen bath at a distance of 5 cm. To prevent microsphere agglomeration, each droplet was equilibrated to liquid nitrogen temperature before adding additional droplets, distinguished by sinking. The droplets solidified on contact with liquid nitrogen, forming spheres, which were placed in a freezer overnight and then freeze-dried for 24 hours.
[0108] Oven drying: Alternatively, chemically treated textiles (2 wt%) in water dispersion were dispersed using a high shear dispersing mixer (Ystral GmbH, Germany) for 20 minutes. The obtained dispersion was cast into a film with a thickness of 1 to 2 cm, which was dried in an oven at 60°C overnight. The dried film was cut into small square pellets (1 cm x 1 cm) using a commercial paper cutter and followed by thermomechanical processing.
[0109] Example 5 - Filament Processing
[0110] • Twin screw extrusion at 225°C to 250°C using fine powder from pellets.
[0111] Example 6 - 3D printing of shoes
[0112] Printer: Ultimaker S5 (Ultimaker BV, The Netherlands).
[0113]
[0114] Table 1. Printing parameters for 3D printing of the sole and straps
[0115] The strip and the sole were printed separately. Both were printed according to the printing parameters presented in Table 1. The only difference was the printing speed of the strip which was set to 50 mm / sec.
[0116] Using 25% polyester cotton / 75% TPU, compression test specimens were printed using filament according to the standard test method D695-15 for compression properties of rigid plastics. The model was designed and printed according to the standard, i.e. in the shape of a cube with dimensions of 12.7 mm × 12.7 mm × 25.4 mm and a print packing density of 10%. The specimens were cut from a mesh sole with a corresponding proportional pore structure. At 30% compression, the compressive strength of the non-porous specimen was about 6 MPa, and for the porous sample, the compressive strength was about 2 MPa.
[0117] Example 7 - 3D Printing of Water Treatment Filters
[0118] 3D Printing: Several different models were 3D printed: (i) a cubic model of standard size (25.4 mm × 12.7 mm × 12.7 mm) for compression testing, (ii) a cubic filter model (20 mm × 20 mm × 20 mm) with different pore structures (i.e., 1 mm, 2 mm, and 3 mm) for adsorption studies. All prototypes were based on cubic and cylindrical computer-aided design (CAD) models. The printing parameters for both custom as well as commercial reference filaments were: nozzle diameter 600 μm, print bed temperature 90 °C, print speed 25 mm / sec, layer thickness 150 μm, shell thickness 500 μm, filling density: 20% to 95% (depending on the model), filling distance: 0.1 mm to 3 mm (depending on the model). The printing temperature was set to 250 °C for both filaments used.
[0119] Compression test: 3D printed cubic specimens (12.7mm×12.7mm×25.4mm) were compression tested according to standard test method D695-15. A 10kN load cell and a compression rate of 1mm / min were applied until 60% deformation was reached. The apparent compressive elastic modulus was calculated from the slope of the linear elastic part of the stress-strain curve without considering the plateau and densification state. The area under the stress-strain curve is considered to calculate the energy dissipation, i.e. the toughness of the sample. The porous composite filter exhibited a compression modulus of 350±39MPa and a strength of 10.6±0.5J / m 3 Toughness.
[0120] Dye adsorption: Testing the 3D printed filter for removal of methylene blue (MB) from water. Using colorimetry (λ 最大 = 664 nm) using an ultraviolet-visible (UV-Vis) spectrophotometer (Genesys TM , 40 / 50, ThermoFisher) to evaluate the removal efficiency. The results showed that although the filter had already removed MB from the water quite effectively after 24 hours of immersion (at 10 mg l -1 80% removal efficiency at immersion temperature), but the results obtained indicate that the oxidized nanofibers are the main adsorption component of the developed filter, since the pure PET filter showed only 10% removal efficiency after immersion for 24 hours.
[0121] Example 8 - Chemical Characterization of Cellulose Fractions in Composites
[0122] Figure 4 The chemical functional groups of cellulose from route ii are shown. FTIR of citrated cotton shows a band at 1670 cm corresponding to the C=O stretching vibration band. -1 Up to 1770cm -1 Broad peak in the range 58,61 ( Figure 4 ). In addition, at 1590cm -1 The band centered corresponds to -CO 2 - asymmetric stretching of the groups), and those seen as part of the ester bonds of cotton (at 1725 cm -1 The ester C=O vibration is centered). These two peaks indicate that the esterification of cellulose was successful and that the carboxyl groups were covalently bonded to the cotton. The total carboxylate charge of the citrated cotton was quantified as 1.1 mmol / g using titration. About 63% of the carboxyl groups came from monoester bonds and 37% from diesters.
[0123] Chemical functional groups of cellulose from pathway iii. The presence of carboxyl groups was confirmed by FTIR. The FTIR spectrum of polyester cotton includes characteristic peaks for both cotton and PET, while the spectra of oxidized polyester cotton and dried polyester cotton pellets include the range 1602 cm -1 Up to 1633cm -1 The additional peak in the TEMPO-mediated oxidation is attributed to the introduction of the sodium salt of the carboxyl group (COO - ) stretching vibration. The charge density of the oxidized polyester cotton was estimated to be 1.2 mmol COO - / g cellulose, indicating that the reaction conditions produced highly charged cellulose fibers.
[0124] Therefore, chemical pretreatment routes (ii) and (iii) are successful in functionalizing cellulose in textiles and textile blends with chemical groups for ionic crosslinking or interaction with water contaminants.During thermomechanical processing, the chemical groups on the cellulose phase will promote fibrillation to the nanoscale.
[0125] Those skilled in the art recognize that the present disclosure is not limited to the above preferred embodiments. For example, those skilled in the art further recognize that modifications and variations are possible within the scope of the appended claims. In addition, those skilled in the art, when practicing the claimed disclosure, can understand and realize changes to the disclosed embodiments from a study of the drawings, the present disclosure, and the appended claims.
Claims
1. A method for melt processing of textile waste, wherein the textile waste comprises: (1) at least one thermoplastic polymer material, such as polyurethane, polyester, nylon, cellulose or elastane; and (2) at least one cellulose-containing material, such as cotton textiles, cotton blends with synthetic polymers or natural polymers, textiles based on regenerated cellulose, suitable for preparing a composite material, comprising the following steps: (a) subjecting the textile waste to a chemical pre-treatment; (b) subjecting the chemically pretreated material of step (a) to thermomechanical processing, including melt compounding, optionally including the addition of recycled PET, plasticizers such as glycerol, PEG and vegetable oils, and / or toughening polymers such as natural rubber and polyurethane; Thereby a composite material comprising a well-dispersed polymer composite and / or nanocomposite is obtained, wherein the at least one thermoplastic polymer material substantially constitutes the matrix phase and the at least one cellulose-containing material substantially constitutes the reinforcement phase of the composite material.
2. The method according to claim 1, wherein the chemical pretreatment is selected from at least one of the following pathways: (i) partially dissolving the at least one thermoplastic polymer material using a 1:1 to 1:2 mixture of TFA (trifluoroacetic acid) and DCM (dichloromethane); (ii) subjecting any cellulose present in the at least one thermoplastic polymer material and / or the at least one cellulose-containing material to citric acid hydrolysis; and (iii) subjecting any cellulose present in the at least one thermoplastic polymer material and / or the at least one cellulose-containing material to a tempo-mediated oxidation.
3. A method according to claim 2, wherein the chemical pretreatment according to route (ii) and / or (iii) is followed by fibrillation using mechanical processing and bead processing using (j) thermally induced phase separation or (jj) oven drying; followed by subsequent thermomechanical processing.
4. A method according to any one of the preceding claims, wherein the textile waste is melt processed at a temperature below 250°C at ambient pressure.
5. The method according to any one of the preceding claims, wherein the cellulose-containing material comprises cellulose I and / or cellulose II polymorphs.
6. A method according to any one of the preceding claims, wherein the textile waste is selected from: recycled textile clothes or shoes; polyester blends; cotton blends containing polyester, elastane, cellulose, polyurethane and / or nylon; chopped polyester cotton; and chopped acrylic cotton.
7. The method according to any one of claims 1 to 6, further comprising using the composite material obtained in step (b) for processing by injection molding, compression molding or any other melt processing method to obtain a recycled product.
8. The method according to any one of claims 1 to 6, further comprising subjecting the composite material obtained in step (b) to filament processing, including filament extrusion to produce 3D printable filaments.
9. The method according to claim 8, further comprising using the obtained 3D printable filament for 3D printing, thereby obtaining a 3D printed recycled product.
10. A composite material comprising a well-dispersed polymer composite and / or nanocomposite, wherein (1) at least one thermoplastic polymer material substantially constitutes a matrix phase, and (2) at least one cellulose-containing material substantially constitutes a reinforcement phase of the composite material, wherein the at least one thermoplastic polymer and the at least one cellulose-containing material are derived from the same textile waste.
11. The composite material according to claim 10, wherein the at least one thermoplastic polymer material is derived from polyurethane, polyester, nylon, cellulose or elastane, and the at least one cellulose-containing material is derived from cotton textiles, cotton blends with synthetic polymers or natural polymers, or regenerated cellulose-based textiles.
12. The composite material according to claim 10 or 11, further comprising (i) recycled PET, (ii) plasticizers such as glycerol, PEG and vegetable oils, and / or (iii) toughening polymers such as natural rubber and polyurethane.
13. A composite material according to any one of claims 10 to 12, wherein the thermoplastic polymer is melt processable at a temperature below 250°C at ambient pressure.
14. The composite material according to any one of claims 10 to 13, wherein the cellulose-containing material comprises cellulose I and / or cellulose II polymorphs.
15. The composite material according to any one of claims 10 to 14, wherein, compared to virgin textile waste, (1) the thermoplastic polymer material is fractionated and the cellulose-containing polymer is intact, or (2) the thermoplastic polymer is intact and the cellulose-containing material is fractionated.
16. The composite material according to any one of claims 10 to 15, comprising nanosized cellulose.
17. The composite material according to any one of claims 10 to 16, wherein the composite material is in the form of pellets.
18. A recycled product comprising the composite material according to any one of claims 10 to 17 further melt processed by injection moulding, compression moulding or any other melt processing method.
19. A 3D printable filament for subsequent use in 3D printing to obtain a 3D printed recycled product, comprising the composite material according to any one of claims 10 to 17 further filament processed by filament extrusion.
20. A 3D printed recycled product comprising the 3D printable filament according to claim 19 which has been further 3D printed.
21. The 3D printed recycled product of claim 20, selected from the group consisting of shoes, clothes, garments, interior design products, accessories or water filters.
Citation Information
Patent Citations
Novel nanoscale plastic particles and preparation method thereof
CN113005536A
Nanofibers from plastic bottles
IN202011022177A
Cotton recycling
US20190136455A1
A process for separation of the cellulosic part from a polyester and cellulose composition
US20210269969A1
Separation of polycotton blends
WO2021181007A1